Betydelsen av skogens ålder och förekomst av lavar för renars val av vinterbetesområde - Esberg, Victoria (2008)
This is a study on winter groups, "siida", of semi-domesticated mountain-migrating reindeers that move to lichen pastures in the lowland boreal forests during winter. The aim of the study was to determine reindeer habitat use in their winter ranges in a managed forest landscape. The reindeers use of three different types of forests was determined, 1) 100-130 year old, 2) 20-40 year old forest and 3) clear-cut areas. All sites were dominated by Scots pine, Pinus sylvestris, and had the same types of ground vegetation. Field inventories of vegetation coverage and proportion consumed lichens was conducted in study plots in early spring. The snow conditions were measured in the middle of February. The 100-130 year old forest and the 20-40 year old forests had the highest mass of lichens per ha. The most Cladonia spp- rich forests are also those most heavily used by winter-feeding reindeers. My results show that reindeers consumed more lichens mass from 100-130 year old pine-forest than from the more dense young, 20-40 year old forest, despite that they are also richer in Cladina spp. One potential explanation for this is that reindeer prefer more open forest because predators are easier to detect in open areas. The clear-felled areas had the lowest lichens mass per ha and the reindeer consumed least lichen mass from these areas, despite the fact that a relatively high proportion of the lichen cover was removed by reindeers. The winter feces of reindeer was more commonly found in the old forest type than in the clear-cuts, also suggesting that these areas were preferred by reindeer. Other studies suggest that reindeers and caribou prefer old forests for foraging when snow depth increase in the winter (Helle 1984, Aspi et al. 1990, Helle et al. 1990, Johnson et al. 2001). Also sámi traditional knowledge by elder reindeer herders in north of Sweden tells us that the best winter habitats for reindeers are dry and lichen rich old pine forests (Inga, 2003). An analysis of the variation in utilization between study plots ...